Material Development of Mutual Cooperation in Akidah ‎Akhlak Subject (Study on Berinjam tradition in ‎ SDN Kuala Jelai)‎ - Alimaturraiyah Alimaturraiyah; Wahab Wahab (Prodi PGMI IAIN Salatiga, 2019)
This study discusses the development of Berinjam material in Akidah Akhlak subject. It is expected that the importance of mutual cooperation material in Akidah Akhlak subject drives students to apply commendable behavior in their daily lives both to themselves and to others. The purpose of this study is to develop teaching materials in the form of lesson plans on the basis of local wisdom. This study used a qualitative method by explaining the development of mutual cooperation material in Akidah Akhlak subject. Based on the findings, Berinjam is a form of sense of helping each other and the community performs its duties properly in accordance with habits and traditions and is carried out jointly. Material development must also refer to the 2013 curriculum. In the matter of mutual cooperation, SD / MI is contained in aspects of morality. The material from Berinjam is intended to make everyone becomes educated in the sense of thinking, listening and be righteous. Berinjam material which is contextualized in mutual cooperation material seizes to shape smart and educated students. In addition, efforts to bring students closer to the peculiarities of the local culture in their homes will not work well if teachers cannot convey it properly. Therefore, teachers must have an adequate understanding of the local cultural values, in addition to their ability to develop the subject matter must be accompanied by contextual so that learning can be achieved. Thus, Berinjam material must be developed through internalization by helping, cooperating and respecting each other.